Cold ischaemia time: Is too long really too bad? Studies using a porcine kidney ex-vivo reperfusion model. (2020) - Hamaoui, Karim; Gowers, Sally; Sandhu, Bynvant; Cook, Terry; Boutelle, Martyn; Casanova-Rituerto, Daniel; Papalois, Vassilios
Abstract: Introduction: Post-ischaemic hypothermic machine perfusion (HMP) may be beneficial in recovery of marginal kidney grafts. The full capacity of conventional HMP (with passive oxygenation) to recondition an organ has not been realised. We investigated whether HMP can ameliorate ischemic damage caused by extremely prolonged static cold storage (SCS). Methods: Porcine kidneys underwent 4-h (SCS4, n = 4) or 52-h (SCS52, n = 4) SCS, followed by 10 h of HMP and were then subjected to 2 h of isolated normothermic reperfusion (NRP). Results: There was a post-SCS graft weight loss in SCS52 vs SCS4 kidneys. SCS52 kidneys showed viable perfusion dynamics during HMP, with significantly shorter times to reach viable parameters vs SCS4 kidneys (p < 0.027). During NRP SCS52 kidneys demonstrated similar trends in perfusion dynamics, renal function, oxygen consumptions, lactate production, and tubular injury to SCS4 kidneys. Conclusion: Graft weight loss after SCS, reducing resistance to perfusion, may facilitate better HMP dynamics and graft reconditioning. Clinicians utilising HMP should be aware of this phenomenon when using HMP in kidneys exposed to extreme periods of SCS. HMP after an extended period of SCS can resuscitate kidneys to a level equitable of viability as those after a short period of SCS. Utilising passive oxygenation however may be limiting such recovery and interventions utilising active oxygenation may provide benefit in such organs. Highlights: SCS flush induced oedema is ameliorated after extended SCS duration. After extreme SCS CIT porcine kidneys demonstrated HMP perfusion dynamics indicative of suitability for transplantation. After extreme SCS CIT kidneys demonstrated similar reperfusion viability profiles to short SCS CIT kidneys.